Modular motor driver with torque control for gripping mechanism - How D.N.T.; Baharuddin M.Z.; Mohideen S.S.K.; Sahari K.S.M.; Anuar A. (Elsevier Ltd, 2023)
This paper presents the algorithms for controlling the torque of a DC motor via a motor driver. Controlling the torque of the DC motor is achieved via PWM variations. The core of the project lies in the capability of the algorithm to regulate PWM to the motor by sensing the average current flow. This algorithm, when implemented on a DC motor that is coupled to a gripping actuator will enable the actuator to have torque control to grasp an object. Torque control algorithm in a gripping actuator will allow sufficient force to be exerted to the object grasped without damaging the object. Apart from that, this algorithm will also protect the hardware of the actuator to ensure it is operating within the continuous current rating of the motor and driver. This is possible by taking in the magnitude of the current drawn by the load as the feedback to the system and set appropriate action to protect the system from damage when a certain setpoint of current is reached. In implementing the project, several algorithms were tested to achieve the torque control algorithm requirement including on-off algorithm, P algorithm, PI algorithm, PD algorithm and PID algorithm. Using the same hardware configuration, the different algorithms produced different outcomes on the output of the controller. The output of the controller is monitored on a computer via serial communication. The serial communication over the USB port on the computer is done by utilizing the Processing programming language and integrated development environment (IDE). This software will enable the output of the controller to be mapped on the computer monitor to provide a real-time graphical view of the output values to the user. These graphical outputs of the controller was evaluated based on the response time, degree of overshooting, and steady-state error to determine the most optimal method of control to be implemented in torque control scheme. The advantage of this method is the minimal cost incurred and the system built does not involve complex feedback system. The application of this system for now is limited to controlling motors connected directly to the load (gripper) without passing through any gear conversions. 2012 The Authors.